(untitled) (Medicine Today, 2025)
Introduction: Musculoskeletal pain is a major cause of disability, affecting joints, bones, muscles, and soft tissues, with prevalence increasing with age. Socio-demographic factors such as age, gender, occupation, and income influence patients’ experiences and satisfaction with physical therapy. Understanding these perceptions is essential for improving treatment outcomes and patient satisfaction. Physical therapy, which includes modalities like thermotherapy and electrotherapy, aims to alleviate pain and enhance recovery. Objective: To find out the patients’ perception on physical therapy treatment of musculoskeletal conditions. Material and Methods: This cross-sectional study was conducted over a one-year period from February 1, 2018, to January 31, 2019, to assess patients’ perceptions of physical therapy treatment for musculoskeletal conditions at the Department of PM&R, BSMMU, Dhaka. The study focused on patients with musculoskeletal pain who sought physical therapy, adhering to specific inclusion and exclusion criteria. Results: The study included 150 patients with a mean age of 40±14.02 years, most of whom were aged 41-50 years. Of the patients, 68% were male and 32% female. The majority lived in Dhaka (42.7%), with 30.7% from semi-urban areas and 26.7% from nearby villages. Marital status showed 80% married and 17.3%unmarried. Most patients received thermotherapy, with 71.3% completing therapies within 10 minutes. Satisfaction levels were generally positive, with 65.3% satisfied with exercise instructions and 66.0% with facilities. Conclusion: This study reveals that most participants were middle-aged males, primarily from the middle-class, with a notable number being housewives. While overall satisfaction with physical therapy services, facilities, and equipment was high, complete satisfaction was less common, particularly with exercise instructions and equipment. Although a few patients deemed the treatment cost unreasonable, the majority were pleased with the environment and privacy measures. Notably, nearly all patients expressed a willingness to continue therapy at the center, reflecting a general satisfaction with the services offered, despite some opportunities for enhancement. Medicine Today 2025, Vol.37 (2): 183-188